Impact of School Closures on the Proportion of Children in the COVID-19 Pandemic: An Example from the Winter Lockdown in Germany - Sorg, Anna-Lisa; Kaiser, Veronika; Becht, Selina; Simon, Arne; von Kries, Rüdiger (Klinische Pädiatrie, 2021)
Background In addition to widely used basic hygiene measures in school, school closures are applied to contain SARS-CoV-2 spread, although the effect on the pandemic is unclear. We proposed a simple approach to disentangle the effect of school closures from other lockdown measures on the pandemic course based on publicly available data in Germany.Methods We used data on the number of SARS-CoV-2 cases from the onset of the pandemic to 14th April 2021. We compared the proportion of children (5–14 years old) in all cases prior to the lockdown measures, including school closure, to that during a ten-week lockdown in Germany. The total number of paediatric cases occurring during lockdown was compared to the number expected in absence of school closures. The latter was calculated based on the actual weekly number of all cases and the pre-lockdown proportion of paediatric cases.Results The proportion of children in all cases was 2.3 percentage points lower at the nadir than the proportion before the lockdown. The estimated total number of paediatric cases prevented by school closures was estimated at 13,246 amounting to 24% of the expected cases in absence of school closures.Conclusion School closure during the winter lockdown reduced the number of expected SARS-CoV-2 cases in children in absence of school closures. The contribution of these prevented cases to the total population incidence is small. These data might provide the basis to model the effect of school closures in addition to basic hygiene measures on the course of the COVID-19 pandemic.Hintergrund Schulschließungen werden neben den herkömmlichen Hygienemaßnahmen (AHA-Regeln) eingesetzt, um die Verbreitung des Virus SARS-CoV-2 einzudämmen. Der Effekt von Schulschließungen auf das Pandemiegeschehen ist derzeit noch nicht ausreichend untersucht. Wir stellen eine einfache Herangehensweise vor, um den Effekt der Schulschließungen, unabhängig von anderen Lockdown-Maßnahmen, auf den Pandemieverlauf abzubilden. Die verwendeten Daten sind in Deutschland öffentlich zugänglich.Methoden Für die Untersuchungen verwenden wir die SARS-CoV-2-Fallzahlen ab Pandemiebeginn bis zum 14. April 2021. Wir verglichen die Fälle unter Kindern (5–14 Jahre) im Verhältnis zu der Gesamtfallzahl vor den Lockdown-Maßnahmen, einschließlich der Schulschließungen, mit dem Verhältnis während des zehnwöchigen Lockdowns in Deutschland. Die absolute Anzahl der pädiatrischen Fälle während des Lockdowns stellten wir der Anzahl der erwarteten Fälle ohne Schulschließungen gegenüber. Letzteres berechneten wir auf Basis der tatsächlichen wöchentlichen Fallzahlen und dem Anteil der pädiatrischen Fälle vor dem Lockdown.Ergebnisse Im Vergleich zum Anteil der pädiatrischen Fälle vor dem Lockdown, verringerte sich dieser während des Lockdowns am Nadir um 2,3 Prozentpunkte. Die geschätzte Anzahl der pädiatrischen Fälle, die durch Schulschließungen verhindert wurden, lag bei 13 246. Dies entspricht 24% der erwarteten Fälle bei einem Verzicht auf Schulschließungen.Schlussfolgerung Schulschließungen während des Winterlockdowns reduzierten die Anzahl der SARS-CoV-2 Fälle unter den Kindern. Im Vergleich mit der Gesamtinzidenz konnte nur eine kleine Anzahl der Fälle verhindert werden. Die Daten können eine Grundlage für ein Modell zur Ermittlung der Auswirkungen von Schulschließungen, neben den herkömmlichen Hygienemaßnahmen (AHA-Regeln), auf den Verlauf der Pandemie darstellen.
Keywords: children; SARS-2; school closure; infection rate